Differences in Erythrocyte Sedimentation Rate (ESR) of Silver Humans Based on Their Working Hours in Semarang City - Gilang Nurwidyansyah; Budi Santosa; Ragil Saptaningtyas (Health Notions, 2023)
Erythrocyte Sedimentation Rate (ESR) is the rate of deposition of erythrocytes in the a tube filled with blood that has been anticoagulated vertical and left for a certain time. Based on the use of materials that silver humans use screen printing paint as a dye and thinner as a paint solvent, The main chemical component of thinner is toluene. Toluene have a high severity of health impacts and if inhaled in the long term will cause an impact serious health problems and can affect erythrocyte sedimentation rate values and sunshine at 12:00 to the afternoon can increases the risk of skin cancer and causes inflammation thus affecting the value of the erythrocyte sedimentation rate. The purpose of this research to measure and analyze differences in sedimentation rate values blood on silver humans based on hours worked in the city Semarang. This type of research was descriptive with a cross-sectional design. Samples were taken as many as 20 silver human samples during working hours at 07:00-12:00 and silver man at hours work at 12:00-17:00 in Semarang City then checked the value of the erythrocyte sedimentation rate using the ESR examination method westergreen. The results showed the average value of erythrocyte sedimentation rate silver man working hours 07:00-12:00 was 11.4 mm/hour, while the average value of the silver human erythrocyte sedimentation rate in hours working hours 12:00-17:00 was 19 mm/hour. Data obtained then analyzed by statistical test Independent Sample T-Test. The results of statistical tests show that there was a difference with p-value of 0.028. The conclusions of this research are: the difference in the value of the erythrocyte sedimentation rate in silver humans in hours working hours 07;00-12:00 and silver man working hours 12:00-17:00 in the city of Semarang. Keywords: erythrocyte sedimentation rate; value; silver man